Comparison of Postoperative Complications after Endoscopic Submucosal Dissection: Differences of Insufflations and Anesthesias. (16th June 2011) - Mori, Hirohito; Kobara, Hideki; Muramatsu, Akemi; Inoue, Hideyuki; Kobayashi, Mitsuyoshi; Nomura, Takako; Hagiike, Masanobu; Izuishi, Kunihiko; Suzuki, Yasuyuki; Gong, Jian; Masaki, Tsutomu
Abstract : Endoscopic submucosal dissection (ESD) has enabled the collective resection and increased the accuracy of pathological diagnosis. However, ESD requires a long operation time, which results in increased doses of analgesics/sedatives, and causes worsening of respiratory and hemodynamic statuses. To reduce postoperative complications, we have applied ESD withCO 2 insufflation and general anesthesia. This study included 50 patients who underwent ESD for early gastric cancer, 25 with air insufflation and intravenous anesthesia (Air/IV group), and the remaining 25 withCO 2 insufflation and general anesthesia (CO 2 /GA group). Postoperative enlarged feeling of the abdomen was observed only in 1 of 25 patients in theCO 2 /GA group (P = 0.0416 ). Postoperative severe unrest was observed in none of the patients in theCO 2 /GA group and in 4 of 25 (16%) patients in the Air/IV group (P = 0.0371 ).CO 2 insufflation and general anesthesia are useful in stabilizing intraoperative conditions and reducing postoperative complications.